KAJIAN YURIDIS UU No. 32 TAHUN 2004 TERHADAP SISTEM PELAKSANAAN FUNGSI ANGGARAN DPRD PROPINSI JAMBI - Kemas Abdul Somad (Universitas Batanghari Jambi, 2014)
The essence of Article 18 of Constitution of 1945 has mandated that areas held autonomous representative body areas, because the government will also jointed area on the basis of deliberation. The significance of the representative body is the attribute of democratization in the regional administration.Basically Indonesian State which adopts a unitary state in the implementation of government was fixed by the applicable law in order to realize the national objectives as defined in the preamble of the Constitution of 1945, with reference to the then drafted the direction of the overall state administration to establish order society, nation and state and to realize progress in all fields. Implementation of state and government in a country not only in the central government alone. Central Government giving authority to local governments to organize their own government. In the State of Indonesia is the local government is the organization of government affairs by the Local Government and Regional Representatives Council (DPRD) in accordance with the principles of autonomy and assistance with the principles of local autonomy as possible.Keyword : government, Rule of Law.